2009
DOI: 10.5194/nhess-9-1291-2009
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Design of rockfall net fences and the new ETAG 027 European guideline

Abstract: Abstract. The need for protection against rockfall has led to the development of different types of technological solutions that are able to both prevent blocks from detaching from rock walls and to control, intercept or deviate the blocks during movement. Of the many devices that are able to intercept and stop a block, one of the most frequently used is net fence. Many different types of full-scale tests have been carried out, with different test site geometries and procedures to study their behaviour and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 16 publications
1
44
0
Order By: Relevance
“…Although it is evident that the impact force induces a complex distribution of stresses within the barrier, the stresses are clearly highest in the region of impact. This is corroborated by the pattern of deformation observed in both physical tests (e.g., Smith and Duffy 1990;Buzzi et al 2012;Peila and Ronco 2009;Peila et al 1998) and numerical simulations (e.g., Hearn et al 1995;Cazzani et al 2002;Anderheggen et al 2002;Grassl et al 2002;Volkwein 2005), where it can be seen the deformation is large in the impacted panel but relatively small in the neighboring panels.…”
Section: Pattern Of Stress and Deformation During Block Impactsupporting
confidence: 62%
See 1 more Smart Citation
“…Although it is evident that the impact force induces a complex distribution of stresses within the barrier, the stresses are clearly highest in the region of impact. This is corroborated by the pattern of deformation observed in both physical tests (e.g., Smith and Duffy 1990;Buzzi et al 2012;Peila and Ronco 2009;Peila et al 1998) and numerical simulations (e.g., Hearn et al 1995;Cazzani et al 2002;Anderheggen et al 2002;Grassl et al 2002;Volkwein 2005), where it can be seen the deformation is large in the impacted panel but relatively small in the neighboring panels.…”
Section: Pattern Of Stress and Deformation During Block Impactsupporting
confidence: 62%
“…The critical energy for a flexible barrier is most reliably determined by physical tests (e.g., Smith and Duffy 1990;Hearn et al 1995;Peila et al 1998;Grassl et al 2002;Bertolo et al 2009;Arndt et al 2009;Hearn et al 1992;Buzzi et al 2012;Peila and Ronco 2009), however large costs and long set-up times have motivated a number studies in which block impact is simulated numerically (e.g., Anderheggen et al 2002;Cazzani et al 2002;Volkwein 2005;Cantarelli et al 2008;Buzzi et al 2011;Hearn et al 1995;Hearn et al 1992). In both tests and simulations, it has been observed that there is no single value of critical energy for a barrier but rather a range of critical energies corresponding to different block sizes.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, probabilistic methods are a suitable approach for modelling rockfall. When risk analysis has to be performed for forecasting and protection purposes, the size of the involved blocks and the corresponding return period are the most important variables among the ones that characterize the phenomenon (Peila et al, 1998(Peila et al, , 2006Peila and Ronco, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour of these works was tackled both by full scale tests (Duffy and Hoon, 1996;Peila et al, 1995Peila et al, , 1998Gottardi and Govoni, 2010;Trad et al, 2011;Buzzi et al, 2013), especially after the development in Europe of the ETAG 027 standards (Peila and Baratono, 2008;Peila and Ronco, 2009), by pseudo-static analyses (Peila et al, 1998;Cantarelli and Giani, 2006) and by numerical modelling (Nicot et al, 2001;Cazzani et al, 2002;Grassl et al, 2002;Volkwein, 2005;Peila et al, 2006;Gentilini et al, 2012Gentilini et al, , 2013Spadari et al, 2012;Escallón and Wendeler, 2013;Escallón et al, 2014;Moon et 10 al., 2014).…”
mentioning
confidence: 99%